Calibration of the momentum scale of a particle physics detector using the Armenteros-Podolanski plot. (28th June 2021) - Baladrón Rodríguez, P.; Chobanova, V.; Cid Vidal, X.; Gligorov, V.; Lucio Martínez, M.; Markov, J.; Martínez Santos, D.; Pló Casasús, M.
Abstract: A method for calibrating the momentum scale in a particle physics detector is described. The method relies on the determination of the masses of the final state particles in two-body decays of neutral particles, which can then be used to obtain corrections in the momentum scale. A modified version of the Armenteros-Podolanski plot and the KS 0 → π + π - decay is used as a proof of principle for this method. A precision at the 10 -6 –10 -8 level is achieved in simplified simulations.